Study of the Best Orientation for Parabolic Concentrator Kind of PolyTrough - Alamen, Sharif Mohamed (European Journal of Sustainable Development, 2014)
In this study, the best guide for Compound Parabolic Concentrator kind of (PolyTrough) has been evaluated by controlling the angle of incidence of beam radiation. The PolyTrough track the radiation of the sun by moving in prescribed ways to minimize the angle of incidence of the beam radiation on their surfaces and thus maximize the incident beam radiation. Tracking systems are classified according to their motions and rotations into five systems and they are: single axis, which is usually horizontal east-west and moving once (system I), continuously ( System II ), horizontal north-south ( system III,IV) moving continuously and parallel to the earth’s axis respectively , or it can be about two axes (system V). We estimated the amount of direct solar radiation in each system controller and then the comparison between the different control methods has been estimated. The results of the study have showed that the system V collects the largest amount of direct solar radiation, but the cost of this system is very expensive due to the presence of two types of collector’s motion. While the fourth (IV) system, is distinguished from the rest of the systems, because it collects a large amount of solar radiation in the winter and decreases in the summer, where this system depends on the angle of the latitude of the site. The control system of the third kind (System III), which is less expensive than the type V and as it moves around one axis only, it collects the amount of solar energy approaching the system V especially in summer. The systems I and II collected values are close to each other, and although that these two systems collect a small amount of the solar radiation during the day comparing to the rest of the systems, this small amount of radiation is considered to be acceptable in the some studied areas. Keywords: PolyTrough, angle of incidence, direct solar radiation